17β-Estradiol Acting as an Electron Mediator: Experiments In Vitro - Getoff, Nikola (2010)
BACKGROUND: The present work reports on the effect of oxidizing (OH, O(2)(•−)) and reducing free radicals (e(−)(aq), H) on 17β-estradiol (17βE2) in respect to breast cancer initiation. The objectives of the study were based on the following premise: the ability of 17βE2 to emit electrons (e(−)(aq)) as well as to transfer them to other biological systems. Thereby, the resulting transient hormone products are leading to the formation of metabolites, some of which may initiate the neoplastic process. The present work considers the effect of the simultaneously generated oxidizing and reducing free radicals on the carcinogenic properties of the 17βE2 metabolites. MATERIALS AND METHODS: Water-soluble 17βE2 with incorporated 2-hydroxypropyl-β-cyclodextrin (HBC) in various aqueous media (pH ~7.4), saturated with air, N(2)O or argon, as well as HBC alone were exposed to the action of free radicals produced by γ-ray. Escherichia coli bacteria (AB 1157) were used as a model for living systems. RESULTS: From the survival curves, obtained under different conditions, the derived ΔD(37) values (representing the radiation dose at which N/N(0) = 0.37; N/N(0) ratio: N(0) = starting number of colonies, N = number after irradiation treatment) illustrate that 17βE2 as well as HBC act as very powerful scavengers of OH and O(2)(•−) radicals. On the other hand, 17βE2 and HBC intermediates resulting from attack of the reducing species (e(−)(aq), H) have strong anticancer properties. CONCLUSION: It is stated that ΔD(37) values strongly depend on the reactivity of the individual free radicals. Oxidizing free radicals lead to positive ΔD(37) values, illustrating the strongly pronounced radiation protecting ability of the systems. On the contrary, the primary reducing free radicals result in negative ΔD(37) values, indicating anticancer effect.